2014
DOI: 10.1177/1933719113519174
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Spindle of Fresh In Vivo-Matured Human Oocytes Through Polarized Light and Confocal Microscopy: A Pilot Study

Abstract: Under the conditions tested, qualitative evaluation of the spindle through PM is not consistent with CM analysis and has limited predictive value of meiotic normality in fresh in vivo-matured human oocytes, which needs to be confirmed in larger studies. Our findings make questionable the usefulness of this methodology as a tool for noninvasive oocyte selection for ICSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…This comparison showed that the non-visualization of the spindle is associated with meiosis abnormalities. This was confirmed by another study, but using oocytes matured in vitro [ 16 ]. This technique could be considered in clinical practice but is costly and requires significant experience.…”
Section: Other Criteria To Assess Oocyte Qualitysupporting
confidence: 71%
“…This comparison showed that the non-visualization of the spindle is associated with meiosis abnormalities. This was confirmed by another study, but using oocytes matured in vitro [ 16 ]. This technique could be considered in clinical practice but is costly and requires significant experience.…”
Section: Other Criteria To Assess Oocyte Qualitysupporting
confidence: 71%
“…De Vos et al . in a randomized sibling‐oocyte study reported that fertilization rate, embryo formation and clinical pregnancy were not different in IMSI and ICSI in male factor patients (De Vos et al ., ). Daniel Luna et al .…”
Section: High Magnification Imaging Systemmentioning
confidence: 97%
“…A notable matter in ICSI by conventional microscopy is damaging the spindle and chromosomes when inserting the ICSI needle into the ooplasm due to unclearing the MS. The location of the first PB is not being a reliable predictor of the MS position, because the MS is not always beneath the first PB (Montag et al, 2011;Dib et al, 2014). Rienzi and associates reported a reduced fertilization rate in oocytes with displacement of the first PB with regard to MS of more than 90° (Rienzi et al, 2003).…”
Section: Spindle Presence/position and Art Outcomesmentioning
confidence: 99%